Hazard identification risk assessment and risk control (HIRARC) pada pembangunan gedung business center - Nustin Merdiana Dewantari; Fajrul Falah; Ani Umyati (Journal Industrial Servicess, 2022)
University Y is currently building a business center building to support lecture activities. Construction of lecture buildings is a must, while construction work is the riskiest job among other jobs. The purpose of this study is to identify potential hazards and reduce workplace accidents in the construction of a business center building and a temporary rest area for workers. This research uses the hazard identification risk assessment and risk control (HIRARC) method, with data collection through observation, interviews, and taking pictures and photos. The results showed that there were 18 potential risks, with low at 33%, moderate at 28%, high at 17%, and extreme at 22%. Risk control can be carried out through technical engineering, administratively by making SOPs, elimination, replacement of tools, and the provision of some personal protective equipment (PPE) that does not yet exist. Supervision of the use of PPE, giving safety signs, and regular meeting activities in the project environment need to be carried out so that workers know the dangers that may arise from their work and be careful at work.